Antiparkinsonian Activity of Benzenesulfonamide Derivatives, Selective MAO-B Inhibitors - Khokhlov, A. L.; Fedorov, V. N.; Shetnev, A. A.; Korsakov, M. K.; Petukhov, S. S.; Vdovichenko, V. P.; Khokhlova, A. A.; Suleimanov, S. Sh (Bulletin of experimental biology and medicine, 2025)
The anti-parkinsonian activity of benzolsulfonamide selective MAO-B inhibitors was evaluated in a model of experimental parkinsonism in white mice (systemic administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine; MPTP). Six candidate compounds (laboratory codes S6-S8 and S11-S13) were analyzed. Rasagiline was used as the reference drug. Only compound S13 was comparable to rasagiline in preventing the development of rigidity and hypokinesia in animals and surpassed the reference drug in correcting emotional and behavioral activity.